Obstacles to the development of workplace health promotion in Poland - the perspective of companies' representatives - Krzysztof Puchalski; Elżbieta Korzeniowska (Nofer Institute of Occupational Medicine, 2020)
Background The aim of the paper is to present the barriers and difficulties faced by companies in Poland in their employee health promotion activities. Material and Methods The aforementioned obstacles were analyzed in terms of their quantity and quality. Quantitative data come from 5 nationwide surveys conducted in 2000 (N = 755), 2006 (N = 611), 2010 (N = 1002), 2015 (N = 1000) and 2017 (N = 1000), in companies employing ≥50 people. Qualitative data were collected from representatives of such companies by means of an audience survey conducted during a conference (N = 75), 8 focus group interviews (N = 64) and individual in-depth interviews (N = 14). Results Invariably, the most frequently reported difficulty has been the shortage of financial resources for health promotion, as well as the lack of real support (legal, fiscal) from the government. By 2017, the former was indicated by 53% of companies, and the latter by 48%. A detailed analysis has shown that they are interrelated, and the key barrier is the mentality of employers and managers, i.e., their reluctance to health promotion, the fact that they are convinced of its high costs, a poor knowledge about its importance and implementation methods, and fear of the unknown. Other difficulties include: culture and work organization not fostering health care, a poor preparation and limited opportunities for the staff to implement health promotion, employees' reluctance to employer's health-related activities, some drawbacks of offers addressed to companies by external service providers, and, to a lesser extent, other difficulties arising from the business environment. Conclusions To effectively mitigate these barriers, it is necessary to involve the government in the implementation of a coherent strategy to support health promotion in companies. Its main directions would be: shaping employers' awareness, supporting health-related activities through fiscal mechanisms (tax and insurance), educating the managerial staff, and pursuing effective cooperation with external providers of health services for employees. Med Pr. 2020;71(5):569-86